The Role Of The School Leader In Managing Conflict At Darussalam Rangae School, Amphoe Rangae, Narathiwat, Thailand - Jih, Potimoh Jih; Amru mayee (The Faculty of Education and Teaching Training, 2024)
Conflict management is nothing but the efforts that need to be made to prevent and avoid conflicts, reduce risks, and not interfere with organizational performance. The purpose of this study is 1) To analyze the actions of the School Principal in managing conflicts between teachers and students, 2) To analyze how the actions of the Principal in managing conflicts between teachers and teachers, 3) To find out the inhibiting and supporting factors of the Principal in managing conflicts that occur in Darussalam School. The approach used in this study is a qualitative approach with a descriptive type of study. The data collection technique uses observation, interview, and documentation techniques. Data analysis used qualitative analysis with the Miles and Huberman model. Data validity uses triangulation of techniques and sources. The results of this study are 1) The action of the Head of School in managing conflicts between teachers and students is to use several stages in managing conflicts, namely identifying conflicts, the next step is reducing conflicts by coordinating, and the last one is resolving the root of the conflict. 2) The action of the Principal in managing conflicts between teachers and teachers is to apply the confrontation approach method, the compromise method, and the integration method. 3) The inhibiting factor in managing conflicts is the existence of parties who do not want to cooperate and cover up the chronology of the conflict. The supporting factors are the teachers' excellent cooperation and a strong sense of kinship. Manajemen konflik tidak lain adalah upaya-upaya yang perlu dilakukan untuk mencegah dan menghindari konflik, mengurangi risiko, dan tidak mengganggu kinerja organisasi. Tujuan dari penelitian ini adalah 1) Untuk menganalisis tindakan Kepala Sekolah dalam mengelola konflik antara guru dengan siswa, 2) Untuk menganalisis bagaimana tindakan Kepala Sekolah dalam mengelola konflik antara guru dengan guru, 3) Untuk mengetahui faktor penghambat dan pendukung Kepala Sekolah dalam mengelola konflik yang terjadi di Sekolah Darussalam. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan tipe penelitian deskriptif. Teknik pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Analisis data menggunakan analisis kualitatif dengan model Miles dan Huberman. Keabsahan data menggunakan triangulasi teknik dan sumber. Hasil dari penelitian ini adalah 1) Tindakan Kepala Sekolah dalam mengelola konflik antara guru dengan siswa adalah dengan menggunakan beberapa tahapan dalam mengelola konflik, yaitu mengidentifikasi konflik, langkah selanjutnya adalah meredam konflik dengan melakukan koordinasi, dan yang terakhir adalah menyelesaikan akar konflik. 2) Tindakan Kepala Sekolah dalam mengelola konflik antara guru dengan guru adalah dengan menerapkan metode pendekatan konfrontasi, metode kompromi, dan metode integrasi. 3) Faktor penghambat dalam mengelola konflik adalah adanya pihak yang tidak mau bekerja sama dan menutup-nutupi kronologi konflik. Faktor pendukungnya adalah kerja sama para guru yang sangat baik dan rasa kekeluargaan yang kuat.